Trophic flexibility and opportunism in pike Esox lucius. Issue 4 (9th September 2015) - Pedreschi, D.; Mariani, S.; Coughlan, J.; Voigt, C. C.; O'Grady, M.; Caffrey, J.; Kelly‐Quinn, M.
<x xml:space="preserve">Abstract</x> The first comprehensive investigation of pike Esox lucius trophic ecology in a region (Ireland) where they have long been thought to be a non‐native species is presented. Diet was investigated across habitat types (lake, river and canal) through the combined methods of stable‐isotope and stomach content analyses. Variations in niche size, specialization and the timing of the ontogenetic dietary switch were examined, revealing pronounced opportunism and feeding plasticity in E. lucius, along with a high occurrence of invertivory (up to 60 cm fork length, LF) and a concomitant delayed switch to piscivory. Furthermore, E. lucius were found to primarily prey upon the highly available non‐native roach Rutilus rutilus, which may alleviate predation pressure on brown trout Salmo trutta, highlighting the complexity of dynamic systems and the essential role of research in informing effective management.